2020
DOI: 10.3346/jkms.2020.35.e240
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of the Children in Disaster: Evaluation and Recovery (CIDER) Protocol for Traumatized Adolescents in Korea

Abstract: Background We aimed to evaluate the feasibility of trauma-focused group therapy in adolescents exposed to traumatic events in Korea. Methods We recruited 22 adolescents (mean age, 16 years; standard deviation, 1.43; range, 13–18 years). Children in Disaster: Evaluation and Recovery (CIDER) V1.0 is a trauma-focused group therapy comprising eight 50-minute-long sessions. The effectiveness of the intervention was evaluated using the Korean version of the Children's Respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 50 publications
0
15
0
1
Order By: Relevance
“…The SES and academic function were categorized into five levels which were ‘high, middle-high, middle, low-middle, and low' according to the student's response as our prior study. 24 25 The survey was conducted from March to October 2017.…”
Section: Methodsmentioning
confidence: 99%
“…The SES and academic function were categorized into five levels which were ‘high, middle-high, middle, low-middle, and low' according to the student's response as our prior study. 24 25 The survey was conducted from March to October 2017.…”
Section: Methodsmentioning
confidence: 99%
“…Thus far, very few studies have evaluated the differences in PTSD symptoms before and after intervention in traumatized adolescents (Choi, 2018). Recently, two studies have evaluated trauma-focused CBT in Korean adolescents diagnosed with PTSD (Lee et al, 2020; Park et al, 2020). Both studies showed a significant improvement of PTSD symptoms and other comorbid psychiatric symptoms.…”
Section: Theoretical and Research Basis For Treatmentmentioning
confidence: 99%
“…Anak-anak seringkali menjadi korban terbesar dalam setiap kejadian bencana akibat ketidakmampuannya melindungi diri dan berada di luar jangkauan pengawasan orangtuanya. Pada saat terjadi bencana, anak-anak juga rentan terhadap penyakit karena daya tahan tubuh mereka yang lemah, sedangkan saat pasca bencana anak-anak seringkali berhadapan dengan dampak bencana seperti sulitnya mendapatkan akses terhadap kebutuhan logistik dan pelayanan kesehatan, rentan mengalami trauma, berisiko terpisah dari keluarganya, serta berpotensi menjadi korban kekerasan ataupun tindak kejahatan (Lee et al, 2020).…”
Section: Pendahuluanunclassified